Electromagnetic Field Analysis of Pumped-Storage Generator-Motor Using Three Dimensional Finite Element Method - Nie, Liangliang; Chen, Man; Zhang, Yujiao; Qin, Weinan; Wu, Xin (Recent Advances in Electrical & Electronic Engineering, 2014)
Pumped-storage power plants are extensively used in power systems because of excellent performances in peak load, frequency regulation and emergency reserve. Generator-motor is an important part of pumped-storage power plant and plays a key role in the operation of the whole power plant, consequently the safety and stability of the power plant and even the power grid are directly influenced by the performance of generator-motor. This paper offers a 3-D eddy current field calculation on generator-motor of Guangzhou Pumped-storage Power Plant B using finite element method (FEM). A 3-D generator-motor model is presented in this paper and the distribution of current density and flux density are educed, as well as the radial air-gap flux density and the harmonic analysis. Through the calculation on 3-D eddy field of generator- motor, electromagnetic distribution, mechanical strength, magnetic flux density and winding current of motor are obtained, offering reference for the design, model selection and localized manufacturing of motor.
Keywords: 3-D calculation